Investigation of the Relationship between Visual Estimation Skills and Spatial Reasoning Skills of Primary School Students - DOĞAN, MİDRABİ CİHANGİR (CUKUROVA UNIV, 2021)
This study aims to examine primary school fourth grade students' visual estimation and spatial reasoning skills. 445 (219 boys and 226 girls) primary school students participated in the study. Correlational model, one of the quantitative research methods, was used to determine the relationship between students' visual estimation skills and spatial reasoning skills. In addition, Spatial Reasoning Skills and Visual Estimation Skills tests were used as data collection tools. Before applying these tests, validity-reliability analyzes were made. The data obtained from the sub-problems of the study were analyzed using different statistical methods such as including one-way multivariate analysis of variance (MANOVA), correlation and path analysis. According to the results of the research, the visual estimation skills and spatial reasoning skills of the students do not differ according to their gender. In addition, it was observed that the scores of the students' spatial reasoning test positively predicted the scores they got from the visual estimation skills test.
Keywords: Visual estimation skills; Spatial Reasoning Skills; Primary School Students; Spatial Visualization; Spatial Orientation; Mental Rotation; SEX-DIFFERENCES; MATHEMATICS; METAANALYSIS; CONNECTION; ABILITY